Pengaruh Media Booklet terhadap Perubahan Pengetahuan dan Sikap Siswa SMU tentang Penyalahgunaan Narkoba - Sapto Adi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This experimental study aimed at investigating the influence of booklet media toward students’ knowledge and attitude toward narcotics abuse. Pre-test post test design was used and the subjects were 40 students who were divided into two groups. One group received information about narcotics abuse and dangerous drugs from booklets and the other did not. Data on students’ knowledge were collected by using learning achievement test, and data on students’ attitude were taken by using Likert attitude scale. Varian analysis was used to analyze data. The result showed that independently, the students’ knowledge and attitude were not different. In pairs, in the treatment group, there was difference in students’ knowledge.